Genetic analyses of pre-meiotic DNA replication in Saccharomyces cerevisiae - Maddinapudi, Sri L P (2015)
Precise and complete replication of the genome is essential for a cell. Chromosome replication follows a defined temporal order, depending on the efficiency and timing of the replication origins. However, the mechanism regulating origin activity has not been properly explained to date. Yeast replication origins are very well characterized and well studied. Genome wide replication in yeast was detailed through deep sequencing in various studies. In yeast, there are multiple replication origins for the complete replication of the genome. In Saccharomyces cerevisiae, there are ~400 replication origins, which are also referred to as Autonomously Replicating Sequences. Replication origins have varied levels of activity and varying times of activation. There are many lines of evidences, which suggest that the origins function differently in mitotic and meiotic cell cycles. It was thought that same origins function both during mitosis and meiosis. However, there is a difference in the replication timings of both the cell cycles, the reason for which is not known. Meiotic cell cycle is longer than the mitotic cell cycle. By using the plasmid-based assays, specific origins were selected and origin activity was analyzed during mitosis and meiosis to see if individual origins show any differences in origin activity. For all the origins tested, the meiotic activity was found to be less than the mitotic activity, which provides a possible explanation for a longer pre-meiotic S phase. Most of the confirmed yeast replication origins are present in the intergenic regions of the chromosome. Due to the presence of majority of replication origins in the intergenic regions and not on the genes, it was thought that the gene transcription might be detrimental to origin activity, hence not supporting the existence of an origin on a gene. Careful analysis of genome wide replication data along with plasmid based ARS assays confirmed that a few replication origins are present within genes. Assays were preformed to study the relation between transcription and origin activity both during mitosis and meiosis. Mitotic origin activity was shown to have no known affect from gene transcription. However, due to some unknown technical faults or other reasons, assays to find out transcription and meiotic activity were not successful.